Algeria : 2016 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the recent economic developments, outlook, risks, and policies required to foster sustainable economic growth of Algeria. Growth was sustained in 2015 while inflation picked up. The budget deficit reached a record high in 2015 because of the collapse in hydrocarbon revenues and a significant fiscal expansion. Beyond 2016, the outlook hinges on the strength of the policy response to the oil price shock. The collapse in oil prices points to the urgent need to reshape Algeria's growth model. Algeria needs to undertake ambitious and sustained consolidation combined with a critical mass of structural reforms to diversify its economy and promote private sector-led growth and job creation.